Elite female basketball players' competitive three-point scoring analysis - Andryushchenko, L. B.; Chernov, S. V.; Markova, A. A.; Andryushchenko, O. N. (Theory and Practice of Physical Culture, 2017)
Successful three-point scoring skills are indispensable in any team`s arsenal since presently the three-point throws account for at least 30% of the best teams` shots, with the shooting success rate varying on average at the same 30%. This is the reason for the high priority being given at present to the three-point shooting success improving tools and methods in the modern basketball theory and practices. Objective of the study was to analyse the competitive three-point scoring statistics of the top-skilled basketball players. The following methods were applied in the study: empirical data collection method including competitive performance (CP) profiling by the game time with video recording data being applied; analysis of formal technical game protocols; educational monitoring of players` CP; scoring metrics i.e. three-point shooting success rates of the top team scorers; and the statistical data processing tools offered by the Microsoft Office Excel 2010.Ink toolkit. Subject to the experiments and analyses under the study were 200 national Premier-League basketball players including 58 best three-point scorers and their CP records as of the season of 2015-16. The study revealed the following results: we identified the factors limiting the competitive three-point scoring success; developed a set of criteria to rate the competitive performance of the three-point scorers; and recommended the coaches to make an emphasis on the three-point scoring attempts with due consideration for the individual conditions and capacities of the team scorers and the game situation tension levels. The study data and analyses made it possible to offer an efficient three-point shooting success improvement method based on a prudent competitive performance management model.